Qualitative Characteristics and Genetic Parameters of F3 Purple Corn Lines from Open Pollination Hybridization - Rima Melati; Eries Dyah Mustikarini; Gigih Ibnu Prayoga (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Purple corn is a cereal plant that has health benefits. Purple corn contains anthocyanins, which are useful as anticancer and antioxidants, and has high nutritional value. Improving the quality of corn production can be done through plant breeding. This study aimed to determine the value of variability, heritability and expected genetic advance of F3 purple corn from open-pollinated hybridization. The research was conducted from December 2020 to April 2021 at Universitas Bangka Belitung. The study used a single plant design experimental method. The selection used was ear to row. The results showed that the color of the seeds of the F3 line was dominated by orange. The lines have different quantitative characters. The lines that have the most purple color were F3-PXU-11-25, F3-PXU-6-16, and F3-PXU-11-20. The value of phenotypic variability and genotypic variability of the broad criteria was found in the weight of corn cob with husk and without husk. The broad heritability was high on the weight corn cob with and without husk. The value of the expected genetic advance progress of the high criteria was on the characters of cob length, the weight of 100 seeds, the weight of corn cob with husk, and the weight of corn cob without husk.